2020
DOI: 10.1111/jcmm.14875
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA hsa_circRNA_002178 silencing retards breast cancer progression via microRNA‐328‐3p‐mediated inhibition of COL1A1

Abstract: Circular RNAs (circRNAs) are a group of non-coding RNAs implicated in the pathogenesis of cancer progression, which exert their functions via regulation of microRNAs (miRNAs) and genes. The present study uses gain-and loss-of-function approaches to evaluate the functions of hsa_circRNA_002178 in angiogenesis along with energy metabolism and underlying downstream signals. The expression pattern of hsa_cir-cRNA_002178 in clinical breast cancer tissues and its association with prognosis were characterized at firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(53 citation statements)
references
References 32 publications
1
52
0
Order By: Relevance
“…8,9 In recent years, the role of circRNA in a variety of diseases has been well documented. 10,11 Some studies have indicated that circRNA can function as an important biomarker for cancer treatment, including OC. 12 Paclitaxel (PTX) is one of the most common chemotherapy drugs used for OC treatment.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 In recent years, the role of circRNA in a variety of diseases has been well documented. 10,11 Some studies have indicated that circRNA can function as an important biomarker for cancer treatment, including OC. 12 Paclitaxel (PTX) is one of the most common chemotherapy drugs used for OC treatment.…”
Section: Introductionmentioning
confidence: 99%
“…CircRNA hsa_circ_0052112 induced breast cancer cell migration and invasion by targeting miR-125a-5p [10]. CircRNA hsa_circRNA_002178 promoted cell viability, tube formation and energy metabolism via up-regulating COL1A1 through miR-328-3p [11]. circ_0072995 is a novel identified circRNA, a recent study found circ_0072995 was elevated in breast cancer cells, and promoted cell metastasis by binding to miR-30c-2-3p in vitro [12].…”
Section: Introductionmentioning
confidence: 99%
“…In this chapter, we ensured that GPX4 was a target of miR-541-3p in HCC cells, cancers. For instance, hsa_circRNA_00278 regulated breast cancer cellular processes via miR-328-3p/COL1A1 axis (Liu, Ye, Ye, Lu, & Han, 2020); hsa_circRNA_0000069 facilitated cervical cancer proliferation and metastasis via miR-873-5p/TUSC3 axis (Zhang, Chen, Sun, An, & Xi, 2020); and circNTRK2 served as a tumorigenic role in esophageal squamous cell carcinoma by sponging miR-140-3p to upregulate NRIP1 (Chen et al, 2020). Similarly, hsa_circRNA_100084/ miR-23a-5p/IGF2 (J.…”
Section: Discussionmentioning
confidence: 99%